[Mission book, North-west Canada] - North-West-America Mission; University of Birmingham Library; Church Mission Society; Adam Matthew Digital (Adam Matthew Digital, 1822)
Ms. copies of papers from the 22nd year (1822) up to 1846. The original papers were copied in full into the mission books so that a legible copy would be available for the use of the Committee